Tackling child sexual abuse : radical approaches to prevention, protection and support - Nelson, Sarah, 1949 November 1- (Policy Press, 2016)
"In this outspoken and challenging book, Sarah Nelson argues that progress in addressing childhood sexual abuse has been in fearful or complacent retreat and that change is urgently needed in order to prevent abuse occurring, and to better support survivors. From this starting point, she puts forward radical suggestions for new models of practice. These are designed to provide perpetrator-focussed child protection, to encourage community approaches to prevention, and to better support those who have survived abuse. As revelations of widespread child abuse continue to emerge at an unprecedented rate, this book campaigns for change, offering policy makers and practitioners solutions for new ways in tackling sexual abuse, working alongside survivors to reduce its prevalence and impact. This book will inspire policy makers, practitioners, academics and journalists to rediscover courage in tackling child sexual abuse. Sarah Nelson proposes new models for child-centred, perpetrator-focussed child protection, for community prevention, and for work with survivor-offenders."--Provided by publisher